Efektifitas tulisan dan gambar peringatan kesehatan pada produk rokok terhadap kesadaran merokok di Kabupaten Badung, Bali-2015 - I Nyoman Gede Suyasa; Desak Gde Diah Dharma Santhi (Intisari Sains Medis, 2018)
Starting in June 2014 tobacco products circulating in Indonesia must be accompanied by pictures and written health warnings. Pictorial warnings can raise public awareness about the impact of smoking, and advocates people to stop smoking. The research objective is to analyze changes in the awareness of smokers after the Ministry of Health policy writing and picture health warnings on the pack of cigarettes. This is an observational study with sample of the population of smokers in Badung. The sample size is 100 people. Sampling is using cluster sampling method, the number of clusters as many as 10 clusters and each cluster includes 10 respondents, 10 clusters selected by PPS. Primary data collection techniques and awareness about the characteristics of smokers using a questionnaire by the officer. Analysis of data using statistical multivariance. The results of the research article health warnings on a cigarette can alter consciousness quit smoking the next 12 months amounted to 74.2% of smokers. Picture health warnings on a cigarette can alter the consciousness of quit smoking the next 12 months amounted to 91.2% of smokers. Cigarettes contain writings average time quitting is 50.42 months and picture health warnings on a cigarette average of 18.78 months to quit smoking. There is a significant difference in the average time a smoker stopped smoking after writing and picture health warnings. We conclude that text health warnings and picture health warnings on a cigarette can raise awareness to quit smoking.